The Art of Moderation in Islamic Semantic Legal Theory: The Case of Yūsuf al-Qaraḍāwī’s Fiqh al-Aqalliyyāt - Muhammad Abdul Aziz (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
Abundant studies on Islamic art have been written, ranging from those based on the dimensions of universality, philosophy, and legal aspects. Yet, how it represents a sense of moderation, which can be found in Islamic semantic legal theory is something underdeveloped. The present research hence aims to reveal this aesthetic dimension examined in the context of Yūsuf al-Qaraḍāwī's jurisprudence for Muslim minorities (fiqh al-aqalliyyāt). Apart from the descriptive analysis, this qualitative research will employ a content analysis method to figure out al-Qaraḍāwī's paradigm in Islamic art, moderation, and fiqh al-aqalliyyāt inherent in his multiple works and interrelate to each other. This study concluded that the aesthetic moderation of the Islamic semantic legal theory lies in the four terms falling under the theory of meaning clarity (naẓariyyat al-wāḍiḥ al-dilālah), i.e., manifest (al-ẓāhir), explicit (al-naṣṣ), unequivocal (al-mufassar), and perspicuous (al-muḥkam). The terms produce beautiful meanings, moving gradually from particularity to universality and corresponding to characters of perfection (symmetrical) and elasticity (asymmetrical). In al-Qaraḍāwī's fiqh al-aqalliyyāt's issues like religious pluralism, greeting other religions' festivals, and democracy, the beauty crystallizes in a thesis that every Muslim must have perfect faith and, at the same time, elastic social association with people of other religions. These findings are expected not only to provide new avenues for the discourse of Muslim minorities but also of Islamic art and semantic law.